2016
DOI: 10.4103/0970-9371.175493
|View full text |Cite
|
Sign up to set email alerts
|

Utility of conventional transbronchial needle aspiration with rapid on-site evaluation (c-TBNA-ROSE) at a tertiary care center with endobronchial ultrasound (EBUS) facility

Abstract: Background:Conventional transbronchial needle aspiration (c-TBNA) is an underutilized bronchoscopic modality. Endobronchial ultrasound (EBUS) guided-TBNA though efficacious is an expensive modality, facilities of which are available at only limited centers. c-TBNA is cost-effective and has potential for wide utilization especially in resource-limited settings. Rapid on-site evaluation (ROSE) improves the yield of c-TBNA.Materials and Methods:A retrospective review of the bronchoscopy records (May 2012 to July … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 13 publications
2
18
0
Order By: Relevance
“…This study also demonstrates the feasibility of safely teaching C-TBNA as part of an algorithmic approach in a teaching center without lengthening procedure times or sacrificing yield and adds to recent reports that yield is maintained with C-TBNA compared to EBUS when C-TBNA is performed by experienced bronchoscopists [23]. …”
Section: Discussionsupporting
confidence: 55%
“…This study also demonstrates the feasibility of safely teaching C-TBNA as part of an algorithmic approach in a teaching center without lengthening procedure times or sacrificing yield and adds to recent reports that yield is maintained with C-TBNA compared to EBUS when C-TBNA is performed by experienced bronchoscopists [23]. …”
Section: Discussionsupporting
confidence: 55%
“…Studies have demonstrated that ROSE can allow reduction of the number of needle punctures, reduction in complication rates, lowering procedure time and costs, and most importantly improving the diagnostic yield. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, in an era of targeted therapy, ROSE is performed to ensure collection of adequate and sufficient material for ancillary studies, including immunohistochemistry (IHC) for subtyping of lung cancer and potential molecular testing in these patients. [8][9][10][11][12] PURPOSE OF ROSE 1. To evaluate sampling adequacy of mediastinal LNs as evidenced by the presence of representative normal tissue (lymphoid tissue or anthracotic pigment-laden macrophages) and/or other lesional material (eg, granulomatous inflammation, malignancy).…”
mentioning
confidence: 99%